Бутилові естери соняшникової олії: синтез, очищення, окисна стабільність - Konovalov, S.V.; Zubenko, S.O.; Patrylak, L.K.; Yakovenko, A.V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2021)
Current paper deals with production, purification and oxidative stability enhancement of fuel-grade sunflower oil butyl esters as more ecological alternative of methyl esters as biodiesel. The oil feedstock, used in this study, included refined sunflower oil (acid value – 0.05 mg KOH/g; 25.3 % of oleic and 61.2 % of linoleic acids) and wasted frying high-oleic sunflower oil (acid value – 1.20 mg KOH/g; 6.1 % of linoleic and 81.7 % of oleic acids). Butanolysis was carried out using potassium butoxide, obtained from KOH and alcohols via original patent-pending method, under mild reaction conditions (alcohol-to-oil molar ratio – 4.5-5.0, 15°C, 1.4-1.6 %еq. KOH of butoxide, 20-30 min). High molar yield of butyl esters (93-96 %) was achieved, while glycerol and vast majority of alkaline catalyst formed the separate reaction products phase mainly in the course of reaction. Ester enriched phases were purified in order to obtain fuel-grade butanol-based biodiesel. Samples after removing of butanol under vacuum followed by water washing and drying were characterized by not enough high butyl esters content (about 94-95 %), as well as higher than allowed content of unconverted glycerides. Vacuum distillation as final purification step allowed fitting butyl esters samples composition within the requirements for biodiesel fuel. Distilled samples contained about 99 % of butyl esters, 0.4-0.5 % of monoglycerides and almost no n-butanol, glycerol, di- and triglycerides. Oxidative treatment (110°C, 6 h, air bubbling) revealed the high oxidation stability of the sample, originated from wasted high-oleic oil, due to the predominance of oleic acid in its fatty acid composition. The sample, obtained from refined sunflower oil (mainly linoleic acid in fatty acid composition), demonstrated very low stability. Addition of at least 2000 mg/kg of antioxidant 2,6-di-tert-butyl-4-methylphenol was shown to be able to improve this characteristic to the level of biodiesel requirements.